Principles of physical chemistry - Maron, Samuel H.; Prutton, Carl F. (New Delhi : Oxford and IBH Publishing Co. Pvt. Ltd., 1965)
Science - General
Includes bibliographical references.
1997-02-19
Keywords: Physical chemistry; Chemistry